TEST EFFECTIVENESS OF BIOLARVASIDES ON THE EXTRACT OF CUCUMBER (Cucumis sativus L.) AND PARE LEAVES (Momordica charantia) ON Aedes aegypti MOSQUITO LARVA - Anisca Defanti Yulistyana; Wildiani Wilson; Arya Iswara (Program Studi Teknologi Laboratorium Medik, 2020)
Dengue fever is a contagious disease in global health problem, especially in developing countries such as Indonesia. Aedes sp is a type of mosquito that can cause dengue fever. Mosquitoes are often associated with health problems due to bites. So the alternative of biolarvaside needed such as cucumber and bitter melon juice which is relatively safe.The objective of this study was to determine the comparison of resistance of Aedes mosquito larvae on cucumber and bitter melon leaves. This research used a natural experiment. The subjects were 576 larvae of Aedes aegypti instar III.The result showed that the extract of bitter melon and cucumber leaves had biolarvaside activation against Aedes sp larvae which was indicated by the highest Aedes sp larvae mortality in bitter melon at all concentrations, whereas for cucumber leaves the death was obtained at a concentration of 30%.It was concluded that the Aedes larvae can not live in the extract of bitter melon leaves compared to cucumber leaves because the extract of the bitter melon concentration was 10%, 20%, 30% and 4 times the larvae totally died.